Nedopingovye sredstva vosstanovlenija v sporte vyssich dostizenij - Kogan, O. S. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The present stage of development of sports of the maximum achievements is characterized by the sharp growth of the volume and intensity of physical loadings. The increased requirements the fulfilling of which is possible only at strict observance of scientifically proved mode of trainings, the obligatory realization of regenerative actions and strict medical control were put in to the organism of an athlete.